Implikasi Instrumen Non-Zakat (Infaq, Sedekah Dan Wakaf) Dalam Perekonomian - Nufi Muï¿½tamar Almahmudi; Nufi Muï¿½tamar Almahmudi (Jurnal Al-Mizan, 2020)
In Islamic economics, zakat is an instrument that has implications for the economy. But there are non-zakat forms which have implications for the economy, namely infaq, alms and endowments. Infaq, alms and endowments are efforts to realize economic justice outside of zakat. This paper tries to present a description related to the implications of non-zakat instruments in the development of sharia economic law on the economy using descriptive analysis methods. With the infaq, alms and endowments instruments means that wealth is distributed from among the rich to the needy. The results of the management of infaq, alms and endowment funds in a productive form can be utilized more broadly in the context of the welfare of the community at large and can be applied as economic development including programs to empower people, alleviate poverty, education, health and others.